Perlindungan Hukum terhadap Eks-Karyawan yang Mengalami Pemutusan Hubungan Kerja dengan Penunggakan Tunjangan - Regina Meylisa Permatasari; Holyness N. Singadimedja; Rafan Darodjat (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2025)
In an employment relationship, there are rights and obligations attached to each party that must be fulfilled. However, in practice, employers often neglect to fulfill the rights of workers during their employment and after termination of employment, even though these obligations are regulated in the Collective Labor Agreement and Joint Agreement. Based on these issues, this study aims to examine and describe the legal protection for former employees who have been terminated with outstanding benefits in accordance with Indonesian labor laws, as well as to obtain an overview of the company's responsibility to fulfill the rights of former employees due to termination of employment in accordance with the agreements in the Collective Labor Agreement and Joint Agreement. This study uses a normative juridical approach based on the provisions of labor laws and regulations. Data was collected through a literature study by examining primary, secondary, and tertiary legal materials relevant to the research issue. All data were then analyzed qualitatively to formulate comprehensive and implementable conclusions and recommendations for the benefit of former employees. The findings show that legal protection for former employees who experience termination of employment with outstanding benefits can be demanded based on labor law regulations in Indonesia. The company has the responsibility and obligation to fulfill the rights of former employees due to termination of employment in accordance with the agreement in the Collective Labor Agreement and Joint Agreement, whereby the payment of these rights must be aligned with and subject to the provisions of applicable laws and regulations.